A Symbiotic Relationship: Reminiscences of the Family. (1st March 2021) - Morris, Joe
Abstract: Architect Joe Morris was a student of Simon Allford and Paul Monaghan's design unit at the Bartlett School of Architecture, University College London. After graduation he joined the still‐small practice and subsequently rose through the ranks before leaving to form his own architectural firm, Morris+Company, which has worked with AHMM on some large urban schemes.